Rapid diagnostics of novel coronavirus infection by loop-mediated isothermal amplification - K. F. Khafizov; V. V. Petrov; K. V. Krasovitov; M. V. Zolkina; V. G. Akimkin (Вопросы вирусологии, 2021)
This review presents the basic principles of application of the loop-mediated isothermal amplification (LAMP) reaction for the rapid diagnosis of coronavirus infection caused by SARS-CoV-2. The basic technical details of the method, and the most popular approaches of specific and non-specific detection of amplification products are briefly described. We also discuss the first published works on the use of the method for the detection of the nucleic acid of the SARS-CoV-2 virus, including those being developed in the Russian Federation. For commercially available and published LAMP-based assays, the main analytical characteristics of the tests are listed, which are often comparable to those based on the method of reverse transcription polymerase chain reaction (RT-PCR), and in some cases are even superior. The advantages and limitations of this promising methodology in comparison to other methods of molecular diagnostics, primarily RT-PCR, are discussed, as well as the prospects for the development of technology for the detection of other infectious agents.